Cenozoic diatreme field in Chubut (Argentina) as an evidence of phreatomagmatic volcanism accompanied with extensive Patagonian plateau basalt volcanism? - Németh, Karoly (2007)
In Patagonia, Argentina, at the northern border of the Patagonian mafic Cenozoic plateau lava fields newly discovered diatremes stand about 100 m above the surrounding plane. These diatremes document phreatomagmatic episodes associated with the formation of the volcanic fields. The identified pyroclastic and intrusive rocks are exposed lower diatremes of former phreatomagmatic volcanoes and their feeding dyke systems. These remotely located erosion remnants cut through Paleozoic granitoids and Jurassic/Cretaceous alternating siliciclastic continental successions that are relatively easily eroded. Plateau lava fields are generally located a few hundreds of metres above the highest level of the present tops of the preserved diatremes suggesting a complex erosional history and potential interrelationships between the newly identified diatremes and the surrounding lava fields. Uprising magma from the underlying feeder dyke into the diatreme root zone intruded the clastic debris in the diatremes, inflated them and mingled with the debris to form subterranean peperite. The significance of identifying diatremes in Patagonia are twofold: 1) in the syn-eruptive paleoenvironment, water was available in various “soft-sediments”, commonly porous, media aquifer sources, and 2) the identified abundant diatremes that form diatreme fields are good source candidates of the extensive lava fields with phreatomagmatism facilitating magma rise with effective opening of fissures before major lava effusions.